The governance of public universities:The missing parameters. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
Despite the recognition of the importance of the public universities ( P U s ) and the increasing complexity of the university business model, the PUs governance system has not changed significantly.